Sosialisasi Pengembangan Kompetensi Bagi Pegawai PPPK Paruh Waktu - Satunggale Kurniawan; Nurri Widianti Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This community service activity was conducted within the Ngawi Regency Government with the aim of improving the understanding and competency of Government Employees with Work Agreements (PPPK) regarding civil servant competency development. The main challenge faced by the partners was the PPPK's limited understanding of policies, mechanisms, and access to competency development programs, which could potentially hinder the optimization of performance and the quality of public services. The implementation method employed an educational-participatory approach through preparation, outreach, mentoring, and evaluation. The activity was conducted in a hybrid format (online and offline) involving hundreds of participants, utilizing the Massive Open Online Course (MOOC) platform as a digital-based learning medium. The results of the activity demonstrated an increased understanding of civil servant management, the role and function of PPPK, and the implementation mechanisms for MOOC-based competency development. Furthermore, this activity successfully created a shared understanding of the rights, obligations, and responsibilities of PPPK within government organizations. Participants' active participation in discussions demonstrated increased awareness and motivation to continuously develop their competencies. The use of digital learning technology also encouraged increased digital literacy among civil servants, a crucial requirement in the era of bureaucratic transformation. Overall, this outreach activity significantly contributed to improving the capacity, professionalism, and commitment of PPPK (Community Empowerment and Child Protection) personnel in supporting the improvement of public service quality and good governance. Therefore, this activity can serve as a model for developing adaptive, sustainable, and relevant civil servant competencies to meet the needs of local government organizations..